2012
DOI: 10.1002/glia.22352
|View full text |Cite
|
Sign up to set email alerts
|

ATP and noradrenaline activate CREB in astrocytes via noncanonical Ca2+ and cyclic AMP independent pathways

Abstract: In neurons, it is well established that CREB contributes to learning and memory by orchestrating the translation of experience into the activity-dependent (i.e., driven by neurotransmitters) transcription of plasticity-related genes. The activity-dependent CREB-triggered transcription requires the concerted action of cyclic AMP/protein kinase A and Ca(2+) /calcineurin via the CREB-regulated transcription co-activator (CRTC). It is not known, however, whether a comparable molecular sequence occurs in astrocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 56 publications
6
27
0
Order By: Relevance
“…We have previously shown that NE and FSK induce CREB-dependent transcription in astrocytes 6 ; here we confirmed that VP16-CREB does as well. Astrocytes infected with Ad2/5-CMV-VP16-CREB at MOIs of 5–30 efficiently transduced VP16-CREB, as deduced by the robust expression of VP16 mRNA and protein detected with Western blotting, immunocytochemistry and qPCR (Fig.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…We have previously shown that NE and FSK induce CREB-dependent transcription in astrocytes 6 ; here we confirmed that VP16-CREB does as well. Astrocytes infected with Ad2/5-CMV-VP16-CREB at MOIs of 5–30 efficiently transduced VP16-CREB, as deduced by the robust expression of VP16 mRNA and protein detected with Western blotting, immunocytochemistry and qPCR (Fig.…”
Section: Resultssupporting
confidence: 87%
“…First, CREB-dependent transcription is activated in astrocytes by noradrenaline (NE), ATP, forskolin (FSK), tamoxifen and cinnamon 68 . NE and ATP act in a protein kinase C-dependent but calcium- and cyclic AMP-independent fashion, FSK activates adenylate cyclase and hence increases cyclic AMP content, whereas tamoxifen and cinnamon act via protein kinase A.…”
Section: Introductionmentioning
confidence: 99%
“…Our study thus supports that cell type and context influence CREB actions, dispelling the widespread notion that there is a canonical CDT represented in neurons or in cell lines like HEK293. In line with this thought, we previously reported that the signaling leading to CREB activation in astrocytes is starkly different to the one documented in neurons (Carriba et al, 2012). Here we extend this observation to show that, like in neurons, the activation of CDT in astrocytes is protective-although through different mechanisms-which calls for combined therapies targeting CREB in both cells in unison.…”
Section: Discussionsupporting
confidence: 85%
“…Primary astrocyte cultures and neuronal cultures were prepared from mouse cortices as previously described (Carriba et al, 2012;Parra-Damas et al, 2014).…”
Section: Culturesmentioning
confidence: 99%
“…For instance, ATP and noradrenaline may cooperate to regulate the transcription of bdnf gene in cortical astrocytes, which could directly influence activity-dependent synaptic plasticity in cortical cells [118]. Besides, it has also been shown that CREB could partially mediate a cGMP/PKG-dependent anti-apoptotic signal in R28 neuroglial progenitor cells [119], and that NO/Ca 2+ -responsive CREB signaling pathway played an important role in regulating endoplasmic reticulum-related cell death in human glioma cells [120].…”
Section: No and Transcription Factor Activation: Creb As A Model In Tmentioning
confidence: 99%